(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Several Russian Hydropower Design and Research Institutes have recently fulfilled studies of hydropower potential estimation for NorthWest, Caucasian and Angara River’s regions in Russia. An approach to automate the calculation of river flow characteristics, based on the usage of annual flow rate map, was proposed and tested by the authors for the aims of the studies.Annual river flow characteristics together with the terrain data are the most important data sources for evaluation of the hydropower potential.A set of requirements was made for the approach and for automation of annual flow rate maps creation in order to provide ability for updates in every 5-10 years.A problem of lack of hydrological data for small and medium sized rivers was faced. To determine the hydrological characteristics the Russian code specification "Determination of Design Hydrological Performance" was used for the conditions of the lack of hydrological data, methods of spatial interpolation were also used.To solve the problems it is necessary to define the parameters of the annual flow distribution: average annual flow, variation coefficient, coefficient of skewness.Mapping is based on the assumption of a smooth change of annual flow rate for any territory in accordance with the distribution of climatic and physiographic factors (topography, soil, groundwater depth, etc.).Milestones of flow rate mapping included: preparation of hydrological initial data; creating of the updated flow rate maps; determination of the corrections to the influence of local azonal factors; estimation of the accuracy of flow characteristics calculations.In order to update the annual flow rate maps a special GIS application “Hydrologist” was created. The GIS application includes computer-assisted tool for processing the hydrological data, import/export tools, tools for analysis of area zoning data, tools for analysis of annual flow rate values in centroids of drainage-basins, location of water stage gauges, also the old and updated flow rate maps.The article deals with the approach description, main problems that were faced and presenting the results.The technology has been applied for North-West, Volga and Siberian Federal Districts in Russia. Comparison of the created annual flow rate map with the previously used map shows that the updated map is better of acquiring hydrological data for small and medium sized rivers.